Microclimate next to the skin: influence on percutaneous absorption of caffeine (ex‐vivo study). Issue 3 (12th December 2013) - Lboutounne, Y.; Silva, J.; Pazart, L.; Bérard, M.; Muret, P.; Humbert, P.
<x xml:space="preserve">Abstract</x> Background/purpose Contact between skin surface and external environment induces a microclimate at the skin surface. That microclimate affects skin interaction with xenobiotics substances. We have developed a new device to explore the influence of environmental parameters, on percutaneous absorption. The aim of this study was to study the influence of external humidity and temperature on percutaneous absorption of caffeine. Methods Six exposure conditions were tested: four by combining two temperatures (27°C and 42°C) with two relative humidities (28% and 70%), performed by our device and two others by using Franz diffusion cell (unoccluded conditions, with skin surface in contact with ambient laboratory environment (27°C/33%) and in occluded conditions with skin surface covering by impermeable membrane). Results Kinetic curve profile of percutaneous absorption of caffeine revealed different shapes characteristics depending on environmental exposure conditions. These profiles were related to evaporative process, of deposited preparation on skin surface combined with water uptake resulting from water flux through skin. Conclusion Our results highlight a preponderant role of microclimate above the skin on percutaneous absorption of caffeine. The device used in this study will be a useful tool to investigate ex vivo, the influence of microclimate on percutaneous absorption.